Muscat of Alexandria in Chile and Argentina: Origin and Relationship with Pisco (Chilean Brandy) [Moscatel de Alejandría en Chile y Argentina: Origen y Relación Con el Pisco] - Lacoste, P (Universidad de Tarapaca, 2015)
This paper explores the origin of the Muscat of Alexandria variety in Chile and its links with Pisco, a brandy typical of the North of Chile, defined as Apellation of Origin in 1931. This variety is important because its crossing with “Pais” grapes originated new cultivars as Moscatel de Austria, Muscatel Amarillo (also called Torontel), Moscatel Rosado and Pedro Giménez. The study was conducted using historical documents preserved in the archives. It was discovered that, in Chile, Muscat of Alexandria started to be grown in La Serena, in the early eighteenth century. However, in the Central Valley, this variety arrived only half a century later. It was also determined that Muscat of Alexandria became linked to the Pisco (Chilean brandy) industry almost since its origins in La Serena, a relation that has remained until today. © 2015, Universidad de Tarapaca. All rights reserved.